The Involvement of Mutual Inhibition of ERK and mTOR in PLCγ1-Mediated MMP-13 Expression in Human Osteoarthritis Chondrocytes - Liu, Zejun (Int J Mol Sci, 2015)
The issue of whether ERK activation determines matrix synthesis or degradation in osteoarthritis (OA) pathogenesis currently remains controversial. Our previous study shows that PLCγ1 and mTOR are involved in the matrix metabolism of OA cartilage. Investigating the interplays of PLCγ1, mTOR and ERK in matrix degradation of OA will facilitate future attempts to manipulate ERK in OA prevention and therapy. Here, cultured human normal chondrocytes and OA chondrocytes were treated with different inhibitors or transfected with expression vectors, respectively. The levels of ERK, p-ERK, PLCγ1, p-PLCγ1, mTOR, p-mTOR and MMP-13 were then evaluated by Western blotting analysis. The results manifested that the expression level of ERK in human OA chondrocytes was lower than that in human normal articular chondrocytes, and the up-regulation of ERK could promote matrix synthesis, including the decrease in MMP-13 level and the increase in Aggrecan level in human OA chondrocytes. Furthermore, the PLCγ1/ERK axis and a mutual inhibition of mTOR and ERK were observed in human OA chondrocytes. Interestingly, activated ERK had no inhibitory effect on MMP-13 expression in PLCγ1-transformed OA chondrocytes. Combined with our previous study, the non-effective state of ERK activation by PLCγ1 on MMP-13 may be partly attributed to the inhibition of the PLCγ1/mTOR axis on the PLCγ1/ERK axis. Therefore, the study indicates that the mutual inhibition of ERK and mTOR is involved in PLCγ1-mediated MMP-13 expression in human OA chondrocytes, with important implication for the understanding of OA pathogenesis as well as for its prevention and therapy.